An interventional study on functional outcome of combined anterior cruciate ligament and anterolateral ligament reconstruction - Jain, Amit Kumar; Yadav, Sudhir Kumar; Modi, Prasant (International Journal of Research in Orthopaedics, 2019)
Background: The anterolateral ligament (ALL) is an important structure for rotational stability of knee joint after anterior cruciate ligament (ACL) rupture. Outcome of combined ACL and ALL reconstruction will change view of high demanding ACL tear cases. Methods: A hospital based prospective interventional study was done in Department of Orthopaedics, SMS Medical College, Jaipur to find the functional outcome of combined anterior cruciate ligament and anterolateral ligament reconstruction. A total of 45 patients underwent ACL and ALL reconstruction. Indications for a combined procedure were associated grade 3 pivot shifts, high level of sporting activity and pivoting sports. Patients were assessed pre- and post-operatively with objective and subjective International Knee Documentation Committee (IKDC) score, Lysholm score, and Tegner activity scale. Results: The mean follow up time was around 5 months. Two patients lost to follow up. Leaving 45 patients for final evaluation. At the last follow-up, all patients had full range of motion. The Lysholm, subjective IKDC, and objective IKDC scores were significantly improved (all p<0.0001). Pre-operatively, 38 patients had a grade 3 pivot shifts and 7 had a grade 2 according to the IKDC criteria. Post-operatively, 42 patients had a negative pivot shift (grade 0), and 3 patients were grade 1 (p<0.0001). Conclusions: This study demonstrates that a combined reconstruction can be an effective procedure without specific complications at a minimum follow-up of 6 months. Longer follow up is required to know any long term complications and functional outcome.